Collectively Exhaustive MXene and Graphene Oxide Multilayer for Suppressing Shuttling Effect in Flexible Lithium Sulfur Battery. Issue 5 (24th October 2021) - Nam, Sanghee; Kim, Jaehwan; Nguyen, Van Hiep; Mahato, Manmatha; Oh, Saewoong; Thangasamy, Pitchai; Ahn, Chi Won; Oh, Il‐Kwon
Abstract: The shuttling effect of lithium polysulfide (LiPS), which leads to the gravest capacity degradation, is one of the critical problems to hindering the commercialization of lithium–sulfur batteries (LSBs). Here, collectively exhaustive Ti3 C2 Tx MXene and graphene oxide (GO) multilayers are reported to suppress the shuttling effect by utilizing both physical inhibition of micro/mesoporous and chemical absorption of surface functional groups. The abundant surface functional groups of GO and MXene attract the positively charged lithium ion (Li + ) and eject the negatively charged polysulfides (S n 2– ) through electrostatic affinity and repulsion. A simple approach using vacuum filtration is utilized to encapsulate elemental sulfur (S8 ) between GO and MXene film (GSM), acting as a permselective separator and functionalized current collector, respectively. The functionally antagonistic GSM directly plays a role in a cathode for LSBs and exhibits a specific capacity of 1425 mAh g –1 at 0.1C in the initial cycle. The abundant functional groups, which can chemisorb the LiPSs, result in a high cyclic retention of ≈85.1% after 500 cycles. Furthermore, a flexible LSB is demonstrated with a PEO‐LiTFSI electrolyte based on the flexibility of the exceptionally thin GSM due to the 2D nanomaterials, MXene and graphene oxide. Abstract : To suppress the shuttling effect of lithium polysulfides through both chemisorption and physical adsorption in lithium sulfur batteries, a functionally antagonistic graphene oxide and Ti3 C2 Tx MXene multilayer that encapsulates elemental sulfur (S8 ) is proposed. The abundant surface functional groups affect the chemisorption of negatively charged polysulfides (S n 2– ) by electrostatic repulsion and Li cations by electrostatic affinity. During 500 cycles, a cyclic retention of 85.1% is obtained, and excellent rate capability at various C‐rates is exhibited.